AN ANALYSIS OF CODE MIXING USED BY BAGUS MULJADI ON PODCAST MAKNA TALKS CHANNELS - Aini, Alvita Farha; Melyana, Mita; Wulandari, Siti; Cahyani, Yunita Lintang; Nargis, Nargis (Media Inovasi Pendidikan dan Publikasi, 2025)
This study analyze the use of code mixing by Bagus Muljadi in the “Makna Talks” podcast episode titled “Talks About the Nation Academic Integrity”. This research utilized a qualitative descriptive approach, this research analyzes the patterns and types of code mixing based on Muysken’s theory, which categorizes code mixing into three types: Insertion, Alternation, and Congruent Lexicalization. Data was collected from a 1:02:30 minute podcast episode that released on June 14th, 2024. The findings revealing the significant instances of code mixing, with Insertion being the most dominant type, followed by Alternation and Congruent Lexicalization. The analysis shows that code mixing serves multiple functions in academic discourse, including expressing technical concepts, maintaining conversation flow, and establishing professional credibility. The study concludes that code mixing in podcast discussions reflects both the evolving nature of Indonesian-English bilingualism and its role in contemporary academic communication.